Optimizing regional allocation of CO2 emissions considering output under overall efficiency. (October 2021) - Zhang, Jingxiao; Jin, Weixing; Yang, Guo-liang; Li, Hui; Ke, Yongjian; Philbin, Simon Patrick
Abstract: Reduction of CO2 emissions is a strategic priority for the construction industry, however current schemes do not provide the level of performance that is required. There is also a lack of understanding of how to allocate CO2 emissions targets within regions. Therefore, this research study develops a three-stage empirical system to identify the CO2 emissions allocation scheme for the Chinese construction industry at the provincial level. The results indicate that (a) the construction industry's CO2 emissions need to be reduced by ca. 10% from the base level in 2017; (b) 86.7% of the provinces have a relatively large capacity for CO2 emissions reduction; (c) China's East region accounts for 44.0% of the total amount for CO2 emissions reduction; and (d) about one-third of the provinces face enormous pressure to reduce CO2 emissions by more than 10% on the base of 2017. This research study provides unique insights and guidance to support assessment of the regional allocation of CO2 emissions for the construction industry, which is a valuable reference for other countries and industries. Highlights: The study develops a three-stage empirical system to identify the CO2 emissions allocation scheme at the provincial level. CO2  emissions need to be reduced by  ca.  10% on the base of 2017. 86.7% of the provinces have a relatively large capacity for CO2 emissions reduction. The East region of China accounts for 44.0% of the total amount of CO2  emissions reduction for the country. About 1/3 of the provinces face major pressure to reduce CO2  emissions by more than 10% on the basis of 2017.